Identification of Funding Sources of Islamic State (Annual of the Faculty of Philosophy in Skopje, 2017)
The purpose of this paper will be focused on investigating the nature of the financing, which is different depending on the type of terrorist organization, where on one hand there are traditional, hierarchically structured terrorist organizations and on the other hand decentralized, networked organizations with an independent financial support, self-management and care of their finances.The Islamic State developed financial independence and acquired economic autonomy which differs significantly from other global terrorist organizations. Given the rapid development of the terrorist organisation the Islamic State in Iraq and the Levant (ISIL), there is a need to understand those funding requirements. ISIL financing is a constantly changing picture and a very difficult and complicated area to address given the operational situation on the ground.The Islamic State represents a new form of terrorist organisation where funding is central and critical to its activities. This paper identifies ISIL ’s primary sources of revenue, which is mainly derivedfrom illicit proceeds from its occupation of territory.The evaluation of the Islamic State finances through traditional approaches towards “countering terrorist finance ” leads to serious misconceptions. The Islamic State is fundamentally different because of the large territory it controls and the unique opportunities that offers for generating income.